Standardization of Research‐Quality Anthropometric Measurement of Infants and Implementation in a Multicenter Study. Issue 4 (5th June 2015) - Coburn‐Miller, Christine; Casey, Susan; Luong, Quynh; Cameron, Natalia; Hocevar‐Trnka, Jasna; Leung, Daniel H.; Gelfond, Daniel; Heubi, James E.; Ramsey, Bonnie; Borowitz, Drucy
Abstract Malnutrition is one of the earliest clinical manifestations of cystic fibrosis (CF) and is associated with poorer pulmonary and cognitive outcomes and survival later in life. Infant growth can be a responsive measure for clinical research in this age group if obtained and characterized accurately. We report here the methods to standardize and implement research‐quality anthropometric measurement of infants with cystic fibrosis in the Baby Observational Nutrition Study multicenter trial.